Kajian Ilmiah: Kontribusi Dana Zakat dalam Program BAZNAS Microfinance Desa terhadap Kesejahteraan Mustahik - Muhammad Wanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Micro-enterprises are small businesses, and poverty in Indonesia is closely linked to their existence. Micro-enterprises face major challenges with capital. It's not uncommon for micro-enterprises to increase their capital to meet their daily needs. Therefore, when there are competing needs, whether for household or business needs, capital needs are usually impacted, and business activities can be temporarily halted. The purpose of this study was to collect and analyze data from articles related to the role of BAZNAS Village Microfinance in the welfare of mustahik (recipients of wealth). The method used in this study was qualitative with the aid of descriptive content analysis. Through a literature review, the author concluded that BAZNAS Village Microfinance plays an effective role in transforming mustahik into muzakki (recipients of wealth) through various strategies, including financial assistance and mentoring for business development. This program improves economic welfare by utilizing zakat funds for empowerment activities, improving their businesses, and providing market access support. It helps beneficiaries effectively promote their products, contributing to poverty reduction and minimizing social inequality.